Incidents associated with mechanical ventilation and intravascular catheters in neonatal intensive care: exploration of the causes, severity and methods for prevention. Issue 2 (24th September 2010) - Snijders, Cathelijne; van Lingen, Richard A; van der Schaaf, Tjerk W; Fetter, Willem P F; Molendijk, Harry A
Abstract : Objectives: To systematically investigate the causes and severity of incidents with mechanical ventilation and intravascular catheters in neonatal intensive care units (NICUs) in the Netherlands, in order to develop effective strategies to prevent such incidents in the future. Design: Prospective multicentre survey. Methods: Inclusion criteria were: incidents with mechanical ventilation and intravascular catheters reported to a voluntary, non-punitive, incident-reporting system which had been systematically analysed using the Prevention Recovery Information System for Monitoring and Analysis (PRISMA)-Medical method. The type, severity and causes of incidents reported from 1 July 2005 to 31 March 2007 are described. Local interventions performed as a result of systematic analysis of incidents are also described. Results: 533 of 1306 (41%) reported incidents with mechanical ventilation and intravascular catheters (n=339/856 and n=194/450, respectively) had been PRISMA analysed and were included in the study. Four incidents resulted in severe harm, 18 in moderate harm and 222 in minor harm. Tube-related incidents accounted for the greatest proportion of harm. 1233 root causes were identified, with most being classified as human error (55%). Of the remaining failures, 20% were organisational, 16% technical, 6% patient-related and 4% unclassifiable. The majority of failures were rule-based errors. Conclusion: Incidents with mechanical ventilation and intravascular catheters occur regularly in NICUs, and frequently harm patients. Multicentre, systematic analysis increases our knowledge of these events. Continuous training and education of all NICU personnel is required, together with preventive strategies aimed at the whole system – including the technical and organisational environment – rather than at human failure alone.